P5 Activity Based on Banyumasan Local Wisdom at the PAUD Institution Sub Topic I Love Banyumas Culture - Mukti Amini; Novan Ardy Wiyani; Murni (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Some teachers still face difficulties implementing local wisdom–based P5 due to limitations in designing culturally based activities. Therefore, this study aims to describe, analyze, and implement a local wisdom–based P5 activity design in early childhood education institutions. This research uses qualitative research methods with the type of applied research. Data were collected by interview, observation and documentation techniques. The data that has been collected is then analyzed using the Miles and Huberman model data analysis techniques. This research is the result of the implementation of the first stage of applied research, where the research is limited to the application of P5 activity design based on the local wisdom of the Banyumasan community on the sub-topic "I Love Banyumas Culture". The result of this first stage of applied research is the formulation of the design of P5 activities based on local community wisdom in early childhood education institutions with the following steps: (1) Formulating the objectives of P5 activities based on local community wisdom; (2) Determine topics and sub-topics that are relevant to concepts or ideas related to the local wisdom of the community; (3) Mapping P5 activity materials based on local community wisdom.; (4) Determining the time allocation for the implementation of P5 activities based on the local wisdom of the community; (5) Prepare a teaching module for P5 activities based on local wisdom of the community with three stages, namely: the stage of knowing the local wisdom, the stage of action the local wisdom, and the stage of reflecting on the local wisdom. It can be concluded that the implementation of P5 activities based on local wisdom produces children with the profile of Pancasila students who love the cultural products of the community.